Design of a Solar‐Wind Hybrid Renewable Energy System for Power Quality Enhancement: A Case Study of 2.5 MW Real Time Domestic Grid - F. Max Savio; S. Vinson Joshua; K. Usha; Muhammad Faheem; Raju Kannadasan; Arfat Ahmad Khan (Engineering Reports)
ABSTRACT The increasing global energy demand driven by climate change, technological advancements, and population growth necessitates the development of sustainable solutions. This research investigates the design, modeling, and simulation of a 2.5 MW solar‐wind hybrid renewable energy system (SWH‐RES) optimized for domestic grid applications. A survey conducted across 450 households identified a total energy demand of 2.3 MW, with distinct day and night usage profiles. In response, a hybrid system consisting of a 1.5 MW solar park and a 1 MW wind energy unit was designed to ensure continuous power supply. The system was modeled and simulated using MATLAB, and its performance was evaluated through a detailed Total Harmonic Distortion (THD) analysis. This research addresses the critical need for a sustainable and high‐quality power supply by designing, modeling, and simulating a 2.5 MW solar‐wind hybrid renewable energy system (SWH‐RES) optimized to meet the energy demand of a surveyed 2.3 MW domestic load, while also reducing THD to acceptable levels for improved power quality and grid stability. The results demonstrated a significant reduction in THD, with voltage THD decreasing from 45.48% to 26.20% and current THD from 8.32% to 2.88% after implementing filtering components. These findings underscore the effectiveness of the proposed SWH‐RES in providing stable, high‐quality power while addressing the growing demand for sustainable energy solutions.